Efeitos da economia solidária sobre a geração de renda e a redução da pobreza: um estudo de dados nacionais - Kuyven, Patricia Sorgatto (Universidade do Vale do Rio dos Sinos, 2016)
This thesis aims to contribute to the study of the Solidarity Economy (SE) to assess its potential as an alternative means for generating jobs and income and may cooperate for the reduction of poverty and misery in Brazil. The Brazilian scenario shows a expressive reduction in the proportion of people in poverty in the last ten years. However, this reduction, so far, has derived mainly from income transfer programs. Thus, the country is eager for a strategy in which people in poverty have access to work, autonomy to rule themselves and their family, making sure they have the necessary skills to achieve the resources needed for their survival. This thesis employs quantitative analysis techniques to assess the impact of solidarity economy on the generation of income among workers from solidarity economic enterprises distributed throughout the country. Two hypotheses are approached in this study: i) performance in EES generates an increase in income for the partners; ii) there are alternative scenarios for the ES, in which the incidence of poverty and extreme poverty could be reduced, generating employment and income. It used a methodology in which a literature review covers issues related to indicators of income and poverty of Brazilians, relevant factors in the generation of income between workers, in addition to describing the panorama of the solidarity economy in the country, including its main features and directions. We conducted a field survey to obtain information from a sample of 2,895 members of solidarity enterprises in the five Brazilian regions. Based on field research results with partners and the data of the Second National Mapping of Solidarity Economic Enterprises conducted by SENAES, the peculiarities and attributes of the public are elucidated. Comparative analyzes were made in order to understand the nuances of Brazilian workers and those specific to the SE, step which made use of micro data from PNAD/IBGE to describe workers in the traditional market. A set of socioeconomic and demographic factors moreover the rationality stemming factors from the solidarity economic enterprises is tested for the purpose of composing an empirical model that determines which factors explain the income of the SEE partners. The model obtained by multiple regression analysis provides the construction and evaluation of SE's operating scenarios for the observation of various conditions for generating income. The regression equation lends itself as a tool for developing an income simulator for workers from solidarity economic enterprises who present different profiles. The simulation makes possible the recognition of the SE higher education performance conditions that provide advances in generating income for its partners. The study results show that the SE contributes significantly to the generation of income in a superior manner to the traditional labor market, especially in often-disadvantaged segments: women, non-white people, rural workers and people with low education. Thus, the SE is set as an effective alternative for reducing poverty rates and misery in the country.
Keywords: Economia solidária; Pobreza; Geração de renda; Trabalho associativo; Análise de regressão; Solidarity economy; Poverty; Generating income; Associated labor; Regression analysis; ACCNPQ::Ciências Humanas::Sociologia